ALTERNATIVE ASSESSMENTS IN TEACHING ENGLISH (Qualitative Research on the Midwifery Program of a University in Bandung) - Deviana Angry Fany, - (2011)
This study is a qualitative study which investigates types of alternative assessments used by teachers in teaching English. This study also investigates the students' responses toward the alternative assessments used by the teachers. The study was conducted in midwifery program of a university in Bandung and participated by 2 teachers and 40 students at the intermediate level. For its framework for analysis, this study implements qualitative approaches to answer the research questions. Observation, document analysis, interview and questionnaire were employed to gain the data. The data were then analyzed in line with the theories used in this study. This study shows that the teachers used three alternative assessments in teaching English that were role-play, oral presentation and exhibition. Most of the students responded positively towards the three alternative assessments. They stated that by having the alternative assessments, learning English be more fun and interesting. Moreover, they said that they could improve their language skills, medical vocabularies in English, and give them descriptions of their strength and weaknesses in English by having the alternative assessments. Besides that, the alternative assessments used by the teachers challenge them to integrate their midwifery knowledge and English skills and to be more active and creative. However, there are some obstacles faced by the students in accomplishing the three alternative assessments. Lack of vocabularies and pronunciation become the most common obstacles found in this study. Based on the findings, it is recommended that alternative assessments to be used to assess students' performance during teaching learning process. It is also important for teachers to be trained and introduced to how to conduct and develop an alternative assessment with its validity and reliability.